2022
DOI: 10.1101/2022.01.24.477490
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Close relatives of MERS-CoV in bats use ACE2 as their functional receptors

Abstract: Middle East Respiratory Syndrome coronavirus (MERS-CoV) and several bat coronaviruses employ Dipeptidyl peptidase-4 (DPP4) as their functional receptors. However, the receptor for NeoCoV, the closest MERS-CoV relative yet discovered in bats, remains enigmatic. In this study, we unexpectedly found that NeoCoV and its close relative, PDF-2180-CoV, can efficiently use some types of bat Angiotensin-converting enzyme 2 (ACE2) and, less favorably, human ACE2 for entry. The two viruses use their spikes' S1 subunit ca… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…However, the receptor for NeoCoV, the closest MERS-CoV relative yet discovered in bats, remains enigmatic [ 6 ]. One recent study, which is yet-to-be peer-reviewed, published in a preprint on the bioRxiv website [ 7 ] has reported that the NeoCoV and its close relative, PDF-2180-CoV, can use some types of bat angiotensin converting enzyme 2 (ACE2) and human ACE2 for its entry. According to the study, the NeoCoV virus uses its spikes’ S1 subunit carboxyl-terminal domains (S1-CTD) for high-affinity and species-specific ACE2 binding.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…However, the receptor for NeoCoV, the closest MERS-CoV relative yet discovered in bats, remains enigmatic [ 6 ]. One recent study, which is yet-to-be peer-reviewed, published in a preprint on the bioRxiv website [ 7 ] has reported that the NeoCoV and its close relative, PDF-2180-CoV, can use some types of bat angiotensin converting enzyme 2 (ACE2) and human ACE2 for its entry. According to the study, the NeoCoV virus uses its spikes’ S1 subunit carboxyl-terminal domains (S1-CTD) for high-affinity and species-specific ACE2 binding.…”
mentioning
confidence: 99%
“…According to the study, the NeoCoV virus uses its spikes’ S1 subunit carboxyl-terminal domains (S1-CTD) for high-affinity and species-specific ACE2 binding. The researchers have discovered a molecular determinant near the viral binding interface that prevents the human ACE2 from promoting NeoCoV infection, particularly around the Asp338 residue [ 7 ]. NeoCoV, on the other hand, infects the human ACE2 expressing cells effectively following a T510F mutation in the receptor-binding motif (RBM) [ 7 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The advantageous effects on LeCR, LCR, and NCR ( 41 , 42 ) present an opportunity to use this glucan as a biomarker in assessing the immune parameters of other β-glucans and immune-enhancing and/or immune-modulating food supplements ( 52 , 53 ). In addition, a rapidly responding immune-modulating capability during COVID-19 infection against a rapid cytokine storm ( 41 , 42 ) simultaneously enhances immune defense and resolves dysfunctions in coagulability ( 67 ) with the combination of two variants.…”
Section: Use Of a Pullulans -Derived β-Glucans As ...mentioning
confidence: 99%